1977
DOI: 10.1056/nejm197705052961801
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Activation of Latent Collagenase by Rheumatoid Synovial Cells

Abstract: To elucidate the mechanism of synovial damage in rheumatoid arthritis, we studied the activation of latent collagenases released from adherent rheumatoid synovial cells in culture. Latent enzyme was not complexed with alpha2 macroglobulin, the prinicpal proteinase inhibitor in serum, and could be activated by trypsin in the presence of alpha2 macroglobulin if sufficient proteinase was added to saturate inhibitor. Latent collagenase bound half as effectively to collagen fibrils as active enzyme. Plasmin was a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
265
0
2

Year Published

1980
1980
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 662 publications
(279 citation statements)
references
References 38 publications
11
265
0
2
Order By: Relevance
“…It has been reported that the zymogens of collagenase and MMP-3 are activated either by direct limited proteolysis by endopeptidases including trypsin, ~-chymotrypsin, plasma kallikrein, plasmin, thermolysin and cathepsin B [12][13][14]18,19], or, alternatively, by mercurial compounds such as NH2PhHgAc that may cause certain conformational changes in the molecule [12][13][14]. The present study has shown for the first time that proMMP-3 can be activated with elastase and cathepsin G from human neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the zymogens of collagenase and MMP-3 are activated either by direct limited proteolysis by endopeptidases including trypsin, ~-chymotrypsin, plasma kallikrein, plasmin, thermolysin and cathepsin B [12][13][14]18,19], or, alternatively, by mercurial compounds such as NH2PhHgAc that may cause certain conformational changes in the molecule [12][13][14]. The present study has shown for the first time that proMMP-3 can be activated with elastase and cathepsin G from human neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…This may well be a component of the plasminogen activator (PA)/plasmin cascade, since plasmin is inhibited by ␣ 1 PI and is a known activator of procollagenases (18)(19)(20)(21). These observations suggest that a furin-dependent activation mechanism occurs early in the cartilage assay, while a serine proteinase pathway, possibly the PA/plasmin cascade, is important later in the cartilage assay.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms of activation of procollagenases in cartilage are not fully understood. The serine proteinase plasmin is a known activator of several proMMPs, including proMMP-1 (collagenase 1), proMMP-13 (collagenase 3), and proMMP-3 (stromelysin 1) (18)(19)(20)(21). MMP-3 itself can activate other proMMPs, including proMMP-1, proMMP-8 (collagenase 2), proMMP-9 (gelatinase B), and proMMP-13 (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…We have shown that both furin-and trypsin-like serine proteinases are involved in the cascades that lead to such activation (148,176), although the precise proteinases involved remain unknown. It has long been established that plasmin can activate procollagenases (36), leading to the suggestion that the PA/plasmin cascade might function in various resorbing tissues to activate proMMPs, including procollagenases (37). A role for this cascade in the activation of endogenous cartilage metalloproteinases was subsequently reported (181,182), and there is also evidence for its presence in invasive rheumatoid synovium (183).…”
Section: Serine Proteinases and Activation Of Procollagenases In Cartmentioning
confidence: 99%
“…The reasons for such conflicting observations are unknown, but the differences may be partly attributable to the different pathologies reported in the models used (32). Furthermore, plasmin has contrasting roles in the context of arthritis: plasmin-mediated fibrinolysis is important in maintaining a healthy joint, while plasmin can also contribute directly to ECM proteolysis by cleaving matrix components (glycoproteins, fibronectin, and proteoglycans) or indirectly by proMMP activation and subsequent ECM degradation (36)(37)(38)(39). Other arthritis-relevant roles for plasmin include intracellular signaling via activation of PAR-1 in association with integrin ␣9␤1 (40), activation of growth factors such as transforming growth factor ␤ (TGF␤) (41,42), release of IGF-1 from IGFBPs (43), and activation of the complement cascade (35).…”
Section: Plasminogen Activator (Pa)/plasmin Cascadementioning
confidence: 99%